Optical processor arrays for controlling focal length or for tuning the depth of field - Ojeda Castaneda, Jorge; Gómez-Sarabia, C. M. (Photonics Letters of Poland, 2011)
We present two families of optical processor arrays. One family uses a pair of complex conjugate phase arrays for implementing a varifocal lenslet array, which is useful for axial scanning. The other family uses a different pair of complex conjugate phase arrays for controlling the depth of field in a telecentric processor array. Full text: PDF References: L. W. Alvarez U.S. Patent 3,305,294 (3rd Dec. 1964). A. W. Lohmann, Italian Patent 727,848 (19th June, 1964). A.W. Lohmann, "A New Class of Varifocal Lenses", Appl. Opt. 9, 1669 (1970). [CrossRef] I. A. Palusinski, J. M. Sasián, and J. E. Greivenkamp, "Lateral-Shift Variable Aberration Generators", Appl. Opt. 38, 86 (1999). [CrossRef] N. López-Gil, H. C. Howland, B. Howland, N. Charman, and R. Applegate, "Generation of third-order spherical and coma aberrations by use of radially symmetrical fourth-order lenses", J. Opt. Soc. Am. A 15, 2563 (1998). [CrossRef] E. R. Dowski, Jr., and T. W. Cathey, "Extended depth of field through wave-front coding.", Appl. Opt. 34, 1859 (1995). [CrossRef] J. Ojeda-Castaneda, J. E. A. Landgrave and C. M. Gómez-Sarabia, "Conjugate phase plate use in analysis of the frequency response of imaging systems designed for extended depth of field", Appl. Opt. 47, (2008). [CrossRef] J. M. Burch and D. C. Williams, "Varifocal moiré zone plates for straightness measurement", Appl. Opt. 16, 2445 (1977). [CrossRef] A.W. Lohmann and D.P. Paris, "Variable Fresnel Zone Pattern", Appl. Opt. 6, 1567 (1967). [CrossRef] E. Acosta and S. Bará, "Variable aberration generators using rotated Zernike plates", J. Opt. Soc. Am. A, 22, 1993 (2005). [CrossRef] S. Bernet and M. Ritsch-Marte, , "Adjustable refractive power from diffractive moiré elements", Appl. Opt. 47, 3722 (2008). [CrossRef] S. Bará, Z. Jaroszewicz, A. Kołodziejczyk, and V. Moreno, "Determination of basic grids for subtractive moire patterns", Appl. Opt. 30, 1258 (1991). [CrossRef]